Balanced Scorecard Design at PT X Construction Services Company - Albert Limanjaya (Universitas Ciputra Surabaya, 2023)
This thesis aims to design a balanced scorecard for PT X, a family-owned construction company which has yet to implement a quantifiable performance evaluation system. The decision to use balanced scorecard is based on the company’s need to create an understanding of its strategy across the company ranks, and to help with strategy execution. This research is conducted based on qualitative methodology, with case study approach. Data collection is done through in-depth interview with the company’s director and managerial staff to better understand the company’s strategic objectives and to set targets based on company’s capability. Data analysis found 13 strategic objectives and 28 indicators across the four perspectives of balanced scorecard.